Plastome Structural Conservation and Evolution in the Clusioid Clade of Malpighiales - Jin, Dong-Min; Jin, Jian-Jun; Yi, Ting-Shuang (Scientific reports, 2020)
The clusioid clade of Malpighiales is comprised of five families: Bonnetiaceae, Calophyllaceae, Clusiaceae, Hypericaceae and Podostemaceae. Recent studies have found the plastome structure of Garcinia mangostana L. from Clusiaceae was conserved, while plastomes of five riverweed species from Podostemaceae showed significant structural variations. The diversification pattern of plastome structure of the clusioid clade worth a thorough investigation. Here we determined five complete plastomes representing four families of the clusioid clade. Our results found that the plastomes of the early diverged three families (Clusiaceae, Bonnetiaceae and Calophyllaceae) in the clusioid clade are relatively conserved, while the plastomes of the other two families show significant variations. The Inverted Repeat (IR) regions of Tristicha trifaria and Marathrum foeniculaceum (Podostemaceae) are greatly reduced following the loss of the ycf1 and ycf2 genes. An inversion over 50 kb spanning from trnK-UUU to rbcL in the LSC region is shared by Cratoxylum cochinchinense (Hypericaceae), T. trifaria and Ma. foeniculaceum (Podostemaceae). The large inversed colinear block in Hypericaceae and Podostemaceae contains all the genes in the 50-kb inversed colinear block in a clade of Papilionoideae, with two extra genes ( trnK-UUU and matK ) at one end. Another endpoint of both inversions in the two clusioids families and Papilionoideae is located between rbcL and accD . This study greatly helped to clarify the plastome evolution in the clusioid clade.